(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study addressed consumer response to television advertising as an influencing factor in impulse buying. The research aimed to determine the impact of advertising on consumer purchasing behavior and the factors influencing impulse buying. A field study was conducted on a random sample of (187) respondents from the city of Baghdad. Observation and questionnaires were used as research tools. The results were statistically analyzed, and several conclusions were reached, the most important of which is that television advertising has an impact on consumer impulse buying through the use of various persuasion methods and the provision of product information. There are also internal factors influencing this, such as personality and needs, and external factors in terms of offers and discounts on products. It was found that there is a significant correlation between television advertising and the factors influencing impulse buying.